Security Issues in Multi-Cloud: A Systematic Literature Review - Drajat Cahya Diningrat; Suhardi; Budi Rahardjo (IEEE Access)
This study aims to systematically review the current literature regarding security concerns in multi-cloud environments. The main objective is to identify critical security issues, current solutions, investigate challenges, and propose recommendations for future research. This study uses a systematic literature review methodology adopting the Kitchenham method, which includes a literature search across leading academic databases including IEEE Xplore, ScienceDirect, ACM, SpringerLink, Emerald Insight, Nature, Taylor & Francis, Scopus, and ProQuest. A formal protocol was followed to conduct an automated search of relevant articles published between 2021 and 2024, and filters were applied. Based on the initial search results, 2038 studies were found, then the selection criteria process (inclusion and exclusion) and quality assessment were carried out, and finally 30 studies were selected for further research. The results show that most of the multi-cloud security issue trends fall into the areas of data, cryptography, authentication and authorization, followed by areas of service availability, confidential computing, and non even fall into the area of virtualization. In addition, this study systematically analyzes the relevant literature and identifies problems, solutions, challenges, and recommendations for future research. The findings of this review are expected to provide a strong overall picture for further research in multi-cloud environments.